Mobile value, spectrum and data demand – a bootstrap approach to estimation. Issue 1 (9th January 2017) - Williamson, Brian; Wood, Sam
Abstract : Purpose: The purpose of this paper is to integrate mobile supply and demand on an economic basis and to model the economic value of additional data capacity, spectrum demand and data growth under a range of parameter and policy assumptions. Design/methodology/approach: The modelling requires an iterative solution to find an equilibrium between supply and demand, which allows data demand to be bootstrapped, i.e. determined endogenously within the model. Findings: The sensitivity of the model to input parameter changes differs from a modelling approach where data demand is assumed to be exogenous, whilst in some instances, the sign of the relationship is reversed, e.g. the response of economic value to mobile site cost changes. Research limitations/implications: The approach suggests a research agenda to estimate willingness to pay for data and the price elasticity of data demand, and may also suggest new explanatory variables to test econometrically in relation to spectrum value. Practical implications: The approach provides a different route to spectrum valuation and allows estimation of the economic impacts of a range of policy questions. Originality/value: This paper provides the integration of supply and demand and endogenous estimation of data demand and economic value, coupled with quantitative assessment of a range of policy questions.